Global activities of mycotoxin societies in safeguarding food and health and future challenges - Antonio F. Logrieco; Sofia Chulze; Benedikt Cramer; Sarah De Saeger; Makoto Kimura; Masayo Kushiro; Peiwu Li; Ronald Maul; Antonio Moretti; Maryam T. Noorabadi; Sheila Okoth; Lindy J. Rose; et al. (Food Control, 2026)

Intercomparison of direct sampling methods of volcanic gases and implications for the determination of chlorine isotopic compositions in fumaroles - E. Le Glas; M. Bonifacie; F. Tassi; G. Bardoux; R. Moretti; V. Robert; E. Chilin-Eusebe; H. Balcone-Boissard; P. Agrinier (Journal of Volcanology and Geothermal Research, 2026)

Navigating urban ecology: Conceptual and methodological insights - Ian MacGregor‐Fors; Christine C. Rega‐Brodsky; D. Johan Kotze; J. Scott MacIvor; Amy K. Hahs; Marco Moretti; Nicholas S. G. Williams; Christopher A. Lepczyk; Kirsten Jung; Madhusudan Katti; Sonja Knapp; Frank A. La Sorte; et al. (Ecology, 2026)
Since its consolidation as a sub‐discipline of ecology in the late 1990s, urban ecology has grown substantially, enhancing our understanding of how urbanization shapes biodiversity and how biodiversity adapts to urbanization. Inherently interdisciplinary in its scope and application, urban ecology is rooted in multiple theoretical and methodological foundations, potentially making the field overwhelming for newcomers as the key literature is scattered across multiple disciplines. Drawing on the collective expertise of editors and reviewers, we attempt to address common pitfalls noted in studies of biodiversity within urban ecosystems and suggest action items for both the new and experienced urban ecologist. Here, we present key concepts for framing hypothesis‐based urban biodiversity research questions, conceptualizing urban settings, accounting for spatial and temporal scales, selecting study systems and meaningful explanatory variables for research questions, and recognizing the social‐ecological nature of urban systems. We offer insights and examples, emphasizing the importance of rigorous urban ecological research without imposing constraints on innovation.

Short-chain PFAS perinatal exposure induces cognitive dysfunction and glial activation in adult rats - G. Foiani; M. Moretti; C. Zanardello; M. Sannia; E. Melchiotti; A. Vitola; F. Gallocchio; L. Lorenzini; L. Giardino; F. Mutinelli; L. Calzà; M. Vascellari (Journal of Comparative Pathology, 2025)

Microplastic pollution in the littoral environment: insights from the largest Mediterranean Sabellaria spinulosa (Annelida) reef and shoreface sediments - Giusto Lo Bue; Maya Musa; Agnese Marchini; Maria Pia Riccardi; Stanislas F. Dubois; Stefania Lisco; Massimo Moretti; Alessia de Luca; Nicoletta Mancin (Marine Pollution Bulletin, 2025)

Protection capacity of Lactiplantibacillus plantarum 83114 against contamination of dry pet food with Aspergillus flavus - Ana F. Moretti; Ángela León Peláez; Marina A. Golowczyc (Animal Feed Science and Technology, 2024)

Factors correlating with circulating T-zone-like cells of undetermined significance (TZUS) in dogs resident in Italy - V. Martini; P. Moretti; F. Sini; A. Ubiali; A. Poggi; F. Riondato (The Veterinary Journal, 2024)

Hepatocellular carcinoma induced by hepatocyte Pten deletion reduces BAT UCP-1 and thermogenic capacity in mice, despite increasing serum FGF-21 and iWAT browning - Álbert S. Peixoto; Mayara F. Moreno; Érique Castro; Luiz A. Perandini; Thiago Belchior; Tiago E. Oliveira; Thayna S. Vieira; Gustavo R. Gilio; Caroline A. Tomazelli; Bianca F. Leonardi; Milene Ortiz-Silva; Luciano P. Silva Junior; et al. (Journal of Physiology and Biochemistry, 2023)

P16-37: Comparative assessment of hepatic in vitro systems for detection of drug-induced liver injury - F. Schwald; J. Velazquez; B. Fischer; M. Rana; M. Goetschy; K. Kubek; F. Moretti (Toxicology Letters, 2023)

Urban forest invertebrates: how they shape and respond to the urban environment - D. Johan Kotze; Elizabeth C. Lowe; J. Scott MacIvor; Alessandro Ossola; Briony A. Norton; Dieter F. Hochuli; Luis Mata; Marco Moretti; Sara A. Gagné; I. Tanya Handa; Therésa M. Jones; Caragh G. Threlfall; et al. (Urban Ecosystems, 2022)
Invertebrates comprise the most diversified animal group on Earth. Due to their long evolutionary history and small size, invertebrates occupy a remarkable range of ecological niches, and play an important role as “ecosystem engineers” by structuring networks of mutualistic and antagonistic ecological interactions in almost all terrestrial ecosystems. Urban forests provide critical ecosystem services to humans, and, as in other systems, invertebrates are central to structuring and maintaining the functioning of urban forests. Identifying the role of invertebrates in urban forests can help elucidate their importance to practitioners and the public, not only to preserve biodiversity in urban environments, but also to make the public aware of their functional importance in maintaining healthy greenspaces. In this review, we examine the multiple functional roles that invertebrates play in urban forests that contribute to ecosystem service provisioning, including pollination, predation, herbivory, seed and microorganism dispersal and organic matter decomposition, but also those that lead to disservices, primarily from a public health perspective, e.g., transmission of invertebrate-borne diseases. We then identify a number of ecological filters that structure urban forest invertebrate communities, such as changes in habitat structure, increased landscape imperviousness, microclimatic changes and pollution. We also discuss the complexity of ways that forest invertebrates respond to urbanisation, including acclimation, local extinction and evolution. Finally, we present management recommendations to support and conserve viable and diverse urban forest invertebrate populations into the future.

Urban biodiversity: State of the science and future directions - Christine C. Rega-Brodsky; Myla F. J. Aronson; Max R. Piana; Ela-Sita Carpenter; Amy K. Hahs; Adriana Herrera-Montes; Sonja Knapp; D. Johan Kotze; Christopher A. Lepczyk; Marco Moretti; Allyson B. Salisbury; Nicholas S. G. Williams; et al. (Urban Ecosystems, 2022)

Involvement of serotonergic neurotransmission in the antidepressant-like effect elicited by cholecalciferol in the chronic unpredictable stress model in mice - Vivian B. Neis; Isabel Werle; Morgana Moretti; Priscila B. Rosa; Anderson Camargo; Yasmim de O. Dalsenter; Nicolle Platt; Axel F. Rosado; William D. Engel; Gudrian Ricardo L. de Almeida; Ingrid Selhorst; Alcir Luiz Dafre; et al. (Metabolic Brain Disease, 2022)

Morpho-sedimentary dynamics of Torre Guaceto beach (Southern Adriatic Sea, Italy) - I Lapietra; S Lisco; G Mastronuzzi; S Milli; C Pierri; F Sabatier; G Scardino; M Moretti (Journal of Earth System Science, 2022)

Antidepressant-like effect of guanosine involves activation of AMPA receptor and BDNF/TrkB signaling - Priscila B. Rosa; Luis E. B. Bettio; Vivian B. Neis; Morgana Moretti; Fernanda N. Kaufmann; Mauren K. Tavares; Isabel Werle; Yasmim Dalsenter; Nicolle Platt; Axel F. Rosado; Daiane B. Fraga; Isabella A. Heinrich; et al. (Purinergic Signalling, 2021)

Protective effect of nutraceutical food on the intestinal mucosa of juvenile pacu Piaractus mesopotamicus under high stocking density - Mariana C. F. Pontin; Wiolene M. Nordi; Jéssica Pampolini; Raul Machado-Neto; Débora B. Moretti (Aquaculture International, 2020)

Long-term chromium picolinate supplementation improves colostrum profile of Santa Ines ewe - Thiago F. V. Bompadre; Débora B. Moretti; Gabriel Z. Sakita; Egon H. Ieda; Maria I. V. Martinez; Elisabete A. N. Fernandes; Raul Machado-Neto; Adibe L. Abdalla; Helder Louvandini (Biological Trace Element Research, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Biotic interactions in species distribution modelling: 10 questions to guide interpretation and avoid false conclusions - Carsten F. Dormann; Maria Bobrowski; D. Matthias Dehling; David J. Harris; Florian Hartig; Heike Lischke; Marco D. Moretti; Jörn Pagel; Stefan Pinkert; Matthias Schleuning; Susanne I. Schmidt; Christine S. Sheppard; et al. (Global Ecology and Biogeography, 2018)
Aim Recent studies increasingly use statistical methods to infer biotic interactions from co‐occurrence information at a large spatial scale. However, disentangling biotic interactions from other factors that can affect co‐occurrence patterns at the macroscale is a major challenge. Approach We present a set of questions that analysts and reviewers should ask to avoid erroneously attributing species association patterns to biotic interactions. Our questions relate to the appropriateness of data and models, the causality behind a correlative signal, and the problems associated with static data from dynamic systems. We summarize caveats reported by macroecological studies of biotic interactions and examine whether conclusions on the presence of biotic interactions are supported by the modelling approaches used. Findings Irrespective of the method used, studies that set out to test for biotic interactions find statistical associations in species’ co‐occurrences. Yet, when compared with our list of questions, few purported interpretations of such associations as biotic interactions hold up to scrutiny. This does not dismiss the presence or importance of biotic interactions, but it highlights the risk of too lenient interpretation of the data. Combining model results with information from experiments and functional traits that are relevant for the biotic interaction of interest might strengthen conclusions. Main conclusions Moving from species‐ to community‐level models, including biotic interactions among species, is of great importance for process‐based understanding and forecasting ecological responses. We hope that our questions will help to improve these models and facilitate the interpretation of their results. In essence, we conclude that ecologists have to recognize that a species association pattern in joint species distribution models will be driven not only by real biotic interactions, but also by shared habitat preferences, common migration history, phylogenetic history and shared response to missing environmental drivers, which specifically need to be discussed and, if possible, integrated into models.

Claviceps arundinis identification and its role in the die-back syndrome of Phragmites australis populations in central Italy - M. Cerri; L. Reale; C. Moretti; R. Buonaurio; A. Coppi; V. Ferri; B. Foggi; D. Gigante; L. Lastrucci; M. Quaglia; R. Venanzoni; F. Ferranti (Plant Biosystems, 2018)

Advanced interpretation of interferometric SAR data to detect, monitor and model ground subsidence: outcomes from the ESA-GMES Terrafirma project - F. Raspini; S. Bianchini; S. Moretti; C. Loupasakis; D. Rozos; J. Duro; M. Garcia (Natural Hazards, 2016)

Monitoring population‐level responses of marine mammals to human activities - Erica Fleishman; Daniel P. Costa; John Harwood; Scott Kraus; David Moretti; Leslie F. New; Robert S. Schick; Lisa K. Schwarz; Samantha E. Simmons; Len Thomas; Randall S. Wells (Marine Mammal Science, 2016)
We provide guidance for monitoring whether human activities affect the physiology or behavior of marine mammals and, if so, whether those effects may lead to changes in survival and reproduction at the population level. We suggest that four elements be included in designing and implementing such a monitoring program. The first is development of a theory of change: a set of mechanistic hypotheses that outline why a given activity might be expected to have one or more measurable effects on individuals and populations, and ideally the magnitude, timing, and duration of the effects. The second element, definition of biologically meaningful effect sizes, ultimately facilitates the development of a monitoring program that can detect those magnitudes of effect with the desired levels of precision. The third element, selection of response variables for monitoring, allows inference to whether observed changes in the status of individuals or populations are attributable to a given activity. Visual observations, passive acoustic and tagging instruments, and direct physical measurements all can provide data that facilitate quantitative hypothesis testing. The fourth element is specification of the temporal sequence of monitoring. These elements also can be used to inform monitoring of the responses of other taxonomic groups to human activities.

Longitudinal HIV-1 gp120-C2V3C3 phylogenetic surveillance and tropism evolution in patients under HAART - Franco A. Moretti; Manuel Gómez-Carrillo; Jorge F. Quarleri (Virus Genes, 2013)

Analysis of the PKR-eIF2alpha phosphorylation homology domain (PePHD) of hepatitis C virus genotype 1 in HIV-coinfected patients by ultra-deep pyrosequencing and its relationship to responses to pegylated interferon-ribavirin treatment - F. Bolcic; M. Sede; F. Moretti; G. Westergaard; M. Vazquez; N. Laufer; J. Quarleri (Archives of Virology, 2012)

Global patterns of stream detritivore distribution: implications for biodiversity loss in changing climates - Luz Boyero; Richard G. Pearson; David Dudgeon; Verónica Ferreira; Manuel A. S. Graça; Mark O. Gessner; Andrew J. Boulton; Eric Chauvet; Catherine M. Yule; Ricardo J. Albariño; Alonso Ramírez; Julie E. Helson; et al. (Global Ecology and Biogeography, 2012)
Aim We tested the hypothesis that shredder detritivores, a key trophic guild in stream ecosystems, are more diverse at higher latitudes, which has important ecological implications in the face of potential biodiversity losses that are expected as a result of climate change. We also explored the dependence of local shredder diversity on the regional species pool across latitudes, and examined the influence of environmental factors on shredder diversity. Location World‐wide (156 sites from 17 regions located in all inhabited continents at latitudes ranging from 67° N to 41° S). Methods We used linear regression to examine the latitudinal variation in shredder diversity at different spatial scales: alpha (α), gamma (γ) and beta (β) diversity. We also explored the effect of γ‐diversity on α‐diversity across latitudes with regression analysis, and the possible influence of local environmental factors on shredder diversity with simple correlations. Results Alpha diversity increased with latitude, while γ‐ and β‐diversity showed no clear latitudinal pattern. Temperate sites showed a linear relationship between γ‐ and α‐diversity; in contrast, tropical sites showed evidence of local species saturation, which may explain why the latitudinal gradient in α‐diversity is not accompanied by a gradient in γ‐diversity. Alpha diversity was related to several local habitat characteristics, but γ‐ and β‐diversity were not related to any of the environmental factors measured. Main conclusions Our results indicate that global patterns of shredder diversity are complex and depend on spatial scale. However, we can draw several conclusions that have important ecological implications. Alpha diversity is limited at tropical sites by local factors, implying a higher risk of loss of key species or the whole shredder guild (the latter implying the loss of trophic diversity). Even if regional species pools are not particularly species poor in the tropics, colonization from adjacent sites may be limited. Moreover, many shredder species belong to cool‐adapted taxa that may be close to their thermal maxima in the tropics, which makes them more vulnerable to climate warming. Our results suggest that tropical streams require specific scientific attention and conservation efforts to prevent loss of shredder biodiversity and serious alteration of ecosystem processes.

Controlling a vancomycin-resistant enterococci outbreak in a Brazilian teaching hospital - M. L. Moretti; L. G. Oliveira Cardoso; C. E. Levy; A. Nowakosky; L. F. Bachur; O. Bratfich; M. L. Leichsenring; R. Fagnani; S. M. Peres Evangelista Dantas; M. R. Resende; P. Trabasso (European Journal of Clinical Microbiology & Infectious Diseases, 2011)

Spider, bee, and bird communities in cities are shaped by environmental control and high stochasticity - T. Sattler; D. Borcard; R. Arlettaz; F. Bontadina; P. Legendre; M. K. Obrist; M. Moretti (Ecology, 2010)
Spatially organized distribution patterns of species and communities are shaped by both autogenic processes (neutral mechanism theory) and exogenous processes (niche theory). In the latter, environmental variables that are themselves spatially organized induce spatial structure in the response variables. The relative importance of these processes has not yet been investigated in urban habitats. We compared the variance explained by purely spatial, spatially structured environmental, and purely environmental components for the community composition of spiders (Araneae), bees (Apidae), and birds (Aves) at 96 locations in three Swiss cities. Environmental variables (topography, climate, land cover, urban green management) were measured on four different radii around sampling points ( Our results suggest that the anthropogenic structuring of urban areas has disrupted the spatial organization of environmental variables and inhibited the development of biotic spatial processes. The near absence of spatial structure may therefore be a feature typical of urban species assemblages, resulting in urban community composition mainly influenced by local environmental variables. Urban environments represent a close‐knit mosaic of habitats that are regularly disturbed. Species communities in urban areas are far from equilibrium. Our analysis also suggests that urban communities need to be considered as being in constant change to adapt to disturbances and changes imposed by human activities.

Sighting characteristics and photo-identification of Cuvier’s beaked whales (Ziphius cavirostris) near San Clemente Island, California: a key area for beaked whales and the military? - Erin A. Falcone; Gregory S. Schorr; Annie B. Douglas; John Calambokidis; Elizabeth Henderson; Megan F. McKenna; John Hildebrand; David Moretti (Marine Biology, 2009)

Determinants for the conservation of a vulnerable fire-dependent species at its marginal range - M. Moretti; C. Staehli; F. Gillet (Plant Ecology, 2008)

Identification of severe potential drug-drug interactions using an Italian general-practitioner database - L. Magro; A. Conforti; F. Del Zotti; R. Leone; M. L. Iorio; I. Meneghelli; D. Massignani; E. Visonà; U. Moretti (European Journal of Clinical Pharmacology, 2008)

Viral outcome of simian–human immunodeficiency virus SHIV-89.6P adapted to cynomolgus monkeys - A. Borsetti; S. Baroncelli; M. T. Maggiorella; S. Bellino; S. Moretti; L. Sernicola; R. Belli; B. Ridolfi; S. Farcomeni; D. R. M. Negri; A. Cafaro; B. Ensoli; et al. (Archives of Virology, 2008)

Importance of species abundance for assessment of trait composition: an example based on pollinator communities - F. Bello; J. Lepš; S. Lavorel; M. Moretti (Community Ecology, 2007)

Within-field variability of Fusarium head blight pathogens and their associated mycotoxins - X.-M. Xu; D. W. Parry; P. Nicholson; M. A. Thomsett; D. Simpson; S. G. Edwards; B. M. Cooke; F. M. Doohan; S. Monaghan; A. Moretti; G. Tocco; G. Mule; et al. (European Journal of Plant Pathology, 2007)

Use and safety profile of antiepileptic drugs in Italy - M. L. Iorio; U. Moretti; S. Colcera; L. Magro; I. Meneghelli; D. Motola; A. L. Rivolta; F. Salvo; G. P. Velo (European Journal of Clinical Pharmacology, 2007)

Evaluation of Fusarium solani Hyphae and Conidia Susceptibility to Amphotericin B and Itraconazole: Study of a Clinical Case - A. B. A. Teixeira; M. L. Moretti; P. Trabasso; A. von Nowakonski; F. H. Aoki; A. C. Vigorito; M. Miyaji; K. Nishimura; H. Taguchi; A. Z. Schreiber (Mycopathologia, 2005)

Potential role of SEN virus on liver enzyme abnormalities in patients positive for hepatitis C virus with or without HIV infection - E. Quiros-Roldan; F. Moretti; C. Torti; V. Tirelli; R. Stellini; S. Pirovano; G. Carosi; L. Imberti (European Journal of Clinical Microbiology & Infectious Diseases, 2005)

Predominance and association of pathogenic fungi causing Fusarium ear blightin wheat in four European countries - X. -M. Xu; D. W. Parry; P. Nicholson; M. A. Thomsett; D. Simpson; S. G. Edwards; B. M. Cooke; F. M. Doohan; J. M. Brennan; A. Moretti; G. Tocco; G. Mule; et al. (European Journal of Plant Pathology, 2005)

Traceability Issues in Fishery and Aquaculture Products - V.M. Moretti; G.M. Turchini; F. Bellagamba; F. Caprino (Veterinary Research Communications, 2003)

The 'BSE Strategic Project' of the National Council of Research: Results of Four Years of Research - F. Valfrè; V.M. Moretti (Veterinary Research Communications, 2003)